A genome‐wide search for quantitative trait loci affecting the cortical surface area and thickness of Heschl's gyrus. (29th August 2014) - Cai, D.‐C.; Fonteijn, H.; Guadalupe, T.; Zwiers, M.; Wittfeld, K.; Teumer, A.; Hoogman, M.; Arias‐Vásquez, A.; Yang, Y.; Buitelaar, J.; Fernández, G.; Brunner, H. G.; et al.
<x xml:space="preserve">Abstract</x> Heschl's gyrus (HG) is a core region of the auditory cortex whose morphology is highly variable across individuals. This variability has been linked to sound perception ability in both speech and music domains. Previous studies show that variations in morphological features of HG, such as cortical surface area and thickness, are heritable. To identify genetic variants that affect HG morphology, we conducted a genome‐wide association scan (GWAS) meta‐analysis in 3054 healthy individuals using HG surface area and thickness as quantitative traits. None of the single nucleotide polymorphisms (SNPs) showed association P values that would survive correction for multiple testing over the genome. The most significant association was found between right HG area and SNP rs72932726 close to gene DCBLD2 (3q12.1; P = 2.77 × 10−7). This SNP was also associated with other regions involved in speech processing. The SNP rs333332 within gene KALRN (3q21.2; P = 2.27 × 10−6) and rs143000161 near gene COBLL1 (2q24.3; P = 2.40 × 10−6) were associated with the area and thickness of left HG, respectively. Both genes are involved in the development of the nervous system. The SNP rs7062395 close to the X‐linked deafness gene POU3F4 was associated with right HG thickness (Xq21.1; P = 2.38 × 10−6). This is the first molecular genetic analysis of variability in HG morphology.